1991
DOI: 10.1212/wnl.41.9.1462
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflexes in patients with diabetes mellitus

Abstract: We evaluated baroreflexes in 58 diabetic and 15 control subjects by determining the latency of response between the end of a Valsalva maneuver (VM) and points on the resultant blood pressure and heart rate (HR) response curves. Prolonged latencies indicative of sympathetic dysfunction were demonstrated in 44% to 88% of diabetic subjects. The results challenge the view that sympathetic dysfunction cannot be detected before parasympathetic abnormalities are manifest. Baroreflex latencies reflected sympathetic dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…An abnormal CRR is often associated with an abnormal blood pressure response to respiratory manoevers and to changes in posture (Ferrer et al 1990;Kennedy et al 1991). The frequency of myocardial infarction and the mortality rate (Niakan et al 1986;Abbot et al 1988) are known to be high among diabetic patients.…”
Section: Influence Of Pancreas Transplantation On Survival Discussionmentioning
confidence: 99%
“…An abnormal CRR is often associated with an abnormal blood pressure response to respiratory manoevers and to changes in posture (Ferrer et al 1990;Kennedy et al 1991). The frequency of myocardial infarction and the mortality rate (Niakan et al 1986;Abbot et al 1988) are known to be high among diabetic patients.…”
Section: Influence Of Pancreas Transplantation On Survival Discussionmentioning
confidence: 99%
“…The high morbidity and mortality of DM is derived from chronic micro and macrovascular complications, 1 as well as alterations in the autonomic neural control of the cardiovascular system. 2,3 Autonomic neuropathy is a common complication of DM that has been found not only in clinical but also in animal models of DM. 2,4 Studies performed in our laboratory on streptozotocin (STZ)-induced diabetic rats showed that they present long-lasting changes in blood pressure, heart rate and autonomic cardiovascular reflexes.…”
Section: Introductionmentioning
confidence: 99%
“…The Finapres has been used in baroreflex studies and has been extensively validated against intra-arterial measurements [8]. While studies of BRS in diabetic subjects have used the Finapres [3] no comparisons with intraarterial measurements have been made. Theoretically, as IDDM can affect vascular reactivity we could simply be detecting an abnormality of the digital arteries rather than a systemic abnormality of cardiovascular control.…”
Section: Discussionmentioning
confidence: 99%
“…With improved technology, baroreceptor-cardiac reflex sensitivity (BRS) is increasingly used to assess autonomic function in diabetic patients [2,3]. Traditionally, BRS is assessed by measuring the changes in R-R interval produced in reflex to acute pharmacologically induced changes in blood pressure [4,5].…”
mentioning
confidence: 99%